MEMBANGUN KEDISIPLINAN KERJA PEGAWAI DAERAH MELALUI PENGAWASAN KERJA EFEKTIF DAN KOMUNIKASI INTERNAL - Eka Putra; Herman Herman (Eko dan Bisnis: Riau Economic and Business Review, 2026)
Abstract : The research was conducted by the Women's Empowerment and Family Planning Agency (BPMPKB) in Kuansing Regency, located in the Kuantan Singingi Regency Government Office Complex. The purpose of this study was to partially determine the effect of supervision and internal communication on the Women's Empowerment and Family Planning Agency (BPMPKB) in Kuansing Regency, and simultaneously to determine the effect of supervision and internal communication on the Women's Empowerment and Family Planning Agency (BPMPKB) in Kuansing Regency. To achieve these objectives, the study used a sample of 32 employees using a census method. Multiple linear regression was used for data analysis. Based on the results of the supervision variable, the calculated t-value was greater than the t-table (2.217 > 2.049). Therefore, it can be concluded that the supervision variable has a positive and significant effect on employee work discipline. The results of the internal communication variable showed a calculated t-value greater than the t-table (2.474 > 2.045). Thus, it can be concluded that internal communication has a positive and significant influence on employee work discipline. The results of the hypothesis test revealed that the most dominant factor influencing employee work discipline is internal communication. A recommendation is that the Kuansing Regency Women's Empowerment and Family Planning Agency (BPMPKB) should focus more on employee supervision, as respondents responded positively. If this is maintained, it will lead to a decrease in employee work discipline.